Pengaruh Kompetensi Dan Reward Terhadap Kinerja Karyawan Pada PT.Bank Muamalat Indonesia (Persero), TBK Bandar Lampung - Muhammad Ridwan; Siti Khoirina (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Worker efficiency is an important part of an organization's tasks. Because the level of progress or decline of the organization depends on it. When representative performance is ineffective, the organization will fail. Work efficiency cannot be separated from the nature of the work. This can be estimated from the abilities of each worker. However, this does not encourage improvements in good company administration. Furthermore, there must be great correspondence and participation between the organization and its workers. Regardless of whether they work for a similar organization. Even so, each worker's presentation is unique. Therefore, pioneers must know this.